A case report on sublingual hematoma - Adil Omar Bahathiq (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2018)
Oral anticoagulants frequently endorsed to treat a thromboembolic occasion or for its prevention. This remedial class, which is a narrow therapeutic index, defended watchful observing, particularly in the principal long stretches of his medicine, and by and large, near patients in whom the draining danger is high (particularly elderly).